Al-induced proteomics changes in tomato plants over-expressing a glyoxalase I gene. (1st April 2020) - Sun, Xudong; Li, Hui; Thapa, Santosh; Reddy Sangireddy, Sasikiran; Pei, Xiaobo; Liu, Wei; Jiang, Yuping; Yang, Shaolan; Hui, Dafeng; Bhatti, Sarabjit; Zhou, Suping; Yang, Yong; et al.
Abstract: Glyoxalase I (Gly I) is the first enzyme in the glutathionine-dependent glyoxalase pathway for detoxification of methylglyoxal (MG) under stress conditions. Transgenic tomato 'Money Maker' plants overexpressing tomato SlGlyI gene (tomato unigene accession SGN-U582631/Solyc09g082120.3.1) were generated and homozygous lines were obtained after four generations of self-pollination. In this study, SlGlyI- overepxressing line (GlyI), wild type (WT, negative control) and plants transformed with empty vector (ECtr, positive control), were subjected to Al-treatment by growing in Magnavaca's nutrient solution (pH 4.5) supplemented with 20 µM Al 3+ ion activity. After 30 days of treatments, the fresh and dry weight of shoots and roots of plants from Al-treated conditions decreased significantly compared to the non-treated conditions for all the three lines. When compared across the three lines, root fresh and dry weight of GlyI was significant higher than WT and ECtr, whereas there was no difference in shoot tissues. The basal 5 mm root-tips of GlyI plants expressed a significantly higher level of glyoxalase activity under both non-Al-treated and Al-treated conditions compared to the two control lines. Under Al-treated condition, there was a significant increase in MG content in ECtr and WT lines, but not in GlyI line. Quantitative proteomics analysis using tandem mass tags mass spectrometry identified 4080 quantifiable proteins and 201 Al-induced differentially expressed proteins (DEPs) in root-tip tissues from GlyI, and 4273 proteins and 230 DEPs from ECtr. The Al-down-regulated DEPs were classified into molecular pathways of gene transcription, RNA splicing and protein biosynthesis in both GlyI and ECtr lines. The Al-induced DEPs in GlyI associated with tolerance to Al 3+ and MG toxicity are involved in callose degradation, cell wall components (xylan acetylation and pectin degradation), oxidative stress (antioxidants) and turnover of Al-damaged epidermal cells, repair of damaged DNA, epigenetics, gene transcription, and protein translation. A protein–protein association network was constructed to aid the selection of proteins in the same pathway but differentially regulated in GlyI or ECtr lines. Proteomics data are available via ProteomeXchange with identifiers PXD009456 under project title '25Dec2017_Suping_XSexp2_ITAG3.2' for SlGlyI- overexpressing tomato plants and PXD009848 under project title '25Dec2017_Suping_XSexp3_ITAG3.2' for positive control ECtr line transformed with empty vector.